Hubungan Persepsi Dokter Tentang Peran Fisioterapi Terhadap Motivasi Memberikan Rujukan ke Unit Fisioterapi (Lembaga Penerbitan Universitas Esa Unggul, 2008)
Ministering activity that is at hospital not despite human resource factor that quality and professional at deep medical activity, as subjective as doctor with fisioterapi.peran doctor in give medical action will involve profession any other in the need recovery accom-plishment patient. It because of marks sense perspsi's relationship doctor. To the effect this research to know picture about doctor perception relationship about physical therapy role to refer patient goes to physical therapy unit at RSUD attacks and RSUD Cilegon by totals sample 48 person. This Observational type utilize cross sectional's research design which is study factor correlation dynamics jeopardy with effect, by observation or data collecting approaching altogether at the moment (point time approch). Base quizs mor-phological result correlation among variable doctor perception about physical therapy role (X) by motivation refer patient go to physical therapy units (Y) at RSUD attacks and RSUD Cilegon, gotten by point r as big as 0,831 where assess r lie on 0,80< KK= 1 and t computing( 10,13) = t table (2,011), therefore Ho is refused. Matter available herculean correlation and happening positive correlation among variable x and variable Y. doctor Perception to physical therapy and Motivation role refers patient to go to influential herculean physical therapy unit, but then to increase doctor perception needs to be done by seminar activity, workshop, socialization about physical therapy by involves go-vernment, doctor, another medical energy and society, so knows problematik's type form whatever available in physical therapy service. Keywords: Perception, Reference, Motivation